Analysis of the quality of students’ sleep and the factors affecting it - Sakalauskaitė, Meda; Mikaliūkštienė, Aldona (Slauga. Mokslas ir praktika, 2023)
Sleep is a natural physiological phenomenon and its influence on the body is felt through various changes in emotional and physical health. It has been proven that regular and quality sleep is associated with better health indicators. Sleep has an impact on memory, concentration, learning process, behavior and quality of life. To maintain optimal health, it is important to sleep enough. Insufficient sleep increases the risk of accidents, injuries, hypertension, obesity, diabetes and depression. The aim of this paper – to review and present the latest literature data on the quality of students’ sleep and the factors influencing it. Methods. A literature search using keywords was conducted in the PubMed, Web of Science databases and in the specialised information search engine Google Scholar, where is written about the quality of student’s sleep and the factors influencing it. The results and conclusions of the study: 45 articles were included in the literature review on the topic under consideration. Based on the research, it has been proven that sleep is important for both emotional and physical human health. The quality of students’ sleep is not good - most of them complain of poor sleep quality, their sleep duration is not sufficient. Stress is one of the factors that impairs the quality of sleep..